Group methodology and women’s access to soft loans in selected microfinance institutions in Edo state, Nigeria (2017)
Group methodology has been identified as one of the key elements that differentiates microfinance from other conventional banks. While financial sustainability remains a necessary goal in microfinance bank, the role of group methodology in contributing to microfinance capital, clients’ access to loans and repayment seem to receive negligible attention. The paper seeks to examine the role of group influence in clients’ access to loans and repayment of loans in Edo state in the bid to experience poverty alleviation. Data were collected using qualitative and quantitative method. This included a survey of 750 purposively selected female clients from six selected microfinance banks in the state, 20 key informant interviews, 14 In-depth interviews and 8 Focus Group discussions (FGDs.) Ninety-eight percent of the respondents revealed that they accessed loans through the microfinance banks and repaid through weekly contributions in their “unions”. Qualitative reports revealed that clients experienced increased solidarity and consistently paid back loans through group influence and sometimes covered up for themselves by paying on behalf of those who default for some unforeseen reasons and get paid among themselves later in other to avoid been disqualified from accessing loans. Key informant interviews revealed that group methodology reduced cost and stress, aided recruitment and training of new members and contributed to finances that serve as loans from potential loanees. Harnessing the potentials of the group to improve business skills and combatt other factors that aggravate the effect of poverty is recommended to make microfinance intervention more impactful